Distribution and structure of Capercaillie (Tetrao urogallus) leks in a Scandinavian mountain range area - Gustafsson, Per-Johan (2008)
The Capercaillie (Tetrao urogallus) is distributed along the whole Scandinavian mountain range, but so far few studies exist about habitat selection, reproductive success, survival rate, lek structure and distribution, etc. of Capercaillie in this region. In this study, I searched for Capercaillie leks during the years 2003-2007 in valleys of the Scandinavian Mountain Range near the village of Tärnaby, Västerbotten County. In total, 20 lek sites were discovered, their locations in the landscape described, and the numbers of territorial males at each lek counted. Within the study area, the influence by forestry so far is small, compared to the situation on lower elevations and in more central part of the boreal forest region where most capercaillie studies have been performed. Observation of Capercaillie males in the study area suggests that the distribution of leks and the number of attending Capercaillie males is different than in other parts of Fennnoscandia. The lek sites were typically found in the upper parts of the coniferous forest, in the edge between the spruce and birch vegetation belts, or in forests mixed with Norway spruce (Picea abies) and birch (Betula pubescens ssp. Czerepanovii). The height of the forest varied from 0 to 25 m, but tree height of 10 to 18 m was preferred in areas of the leks. In lower parts of the valley, leks were also found in broader belts of coniferous forest.